The Influence Of Classic Music On Emotion Regulation In English Students, Uigm Palembang University, 2022 - Pratiwi, Hanni; Iqbal, Iqbal Andriano; Fatimah Az - zahra (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
Students are transitioning from adolescence to early adulthood where controlling emotional regulation is still very difficult,Failure to process these emotions can make you aggressive and apathetic. The aim to be achieved in this research is to determine the effect of providing classical music on the emotional regulation of students at UIGM Palembang. This research is experimental research that uses a two group pretest-posttest research design. The research subjects were 20 students from UIGM Palembang aged 19-21 years. The data collection method in this research uses a psychological scale, namely a 12-item emotional regulation scale. Data analysis using the non-parametric Wilcoxon Signed Ranks statistical test technique produced a sig value of 0.025, a Z score value of -2.809 and a mean rank at the pretest of 0.87 while the posttest was 1.38. It can be concluded that there was a significant change in emotional regulation between the pretest and posttest of the experimental group after being given treatment in the form of listening to classical music.